Properties of bio-pellets obtained from walnut and peanut shells - Üçok, Serdar (International Journal of Agricultural and Biological Engineering, 2024)
Energy is considered a measure of development in today’s world. In recent years, the increasing global population has led to a growing demand for energy. Due to the limited availability of fossil fuels and the environmental harm they cause, there has been a shift towards renewable energy sources worldwide. Among these renewable energy sources, biomass technology is clean, eco-friendly, and highly energy-efficient. Its implementation not only contributes to energy production but also plays a significant role in rural development. Within the realm of biomass, the production of bio-pellets is essential for the sustainable utilization of healthy, eco-friendly, and organic waste materials for energy purposes. The pelletization process offers several advantages, including an increase in the volumetric heat value of the material, reduced transportation and storage costs, improved combustion characteristics, and a decrease in particle emissions into the atmosphere. This study focuses on the production of bio-pellets by mixing walnut shell (WS) and peanut shell (PS) materials in five different ratios (100% WS, 50% WS+50% PS, 75% WS+25% PS, 25% WS+75% PS, 100% PS). The moisture content, ash content, volatile matter content, fixed carbon content, and drop resistance of the obtained pellets have been determined.Keywords: walnut shell, peanut shell, bio-pellet, energyDOI: 10.25165/j.ijabe.20241706.9054Citation: Üçok S. Properties of bio-pellets obtained from walnut and peanut shells. Int J Agric & Biol Eng, 2024; 17(6): 281–285.